AN ASSESSMENT OF ANIMAL PROTEIN CONSUMPTION PATTERNS AMONG RURAL DWELLERS IN OSUN STATE, NIGERIA - Adekunmi, A O; Ayinde, J O; Ajala, A O (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2017)
The study assessed animal protein consumption patterns among rural dwellers in Osun State,Nigeria. A multi-stage sampling technique was employed to select 120 respondents. Datacollected were described using frequency count, percentage, means and standard deviation.Multiple regression and chi square analyses were used to explain the relationships betweensocio-economic characteristics and rural dwellers’ consumption patterns of animal proteins. Themean age of respondents was 27.4 years while 57.5 percent, 42.5 percent were males and femalesrespectively. Also 66.7 percent were married while 88.3 percent had formal education rangingfrom primary to tertiary education. More than half (69.2%) of the respondents had between 5 and8 household members. Farming was the major occupation of 75.0 percent of the respondents. Themost consumed animal protein sources were fish (41.0%), milk (42.0%) for breakfast, while fordinner, beef (62.2%), fish (45.1%) were the major sources of animal protein consumption,chickens were not commonly consumed by rural households because it is only during festivalsthat chickens are commonly consumed. The results of the co-efficient of multiple regression (R2)showed that 83 percent variation in the dependent variable was explained by the independentvariables included in the regression model. The co-efficient of age (X1) showed a negative (b =-0.063) relationship to the dependent variable, likewise, sex (b =- 0.108), religion and occupation(b =- 0.146) were not statistically significant to animal protein consumption patterns of therespondents. However, marital status (b = 0.142, p < 0.01), educational status (b = 0.114, p <0.01), household size (b = 0.146, p < 0.01) and household income per annum (b = 0.262 p<0.01) were statistically significant. It was recommended that government and non-governmentorganizations should intensify nutrition campaigns to rural dwellers that would help in enlightenthem on the importance of protein of animal sources in their diets.